محددات الإستعمال المتزايد للسيولة النقدية في الإقتصاد الوطني: دراسة للفترة من 2000- 2014 - صاري، علي; البحري، عبدالله Albahari, Abdullah (المركز الجامعي أمين العقال الحاج موسى أق أخموك لتامنغست - معهد الحقوق والعلوم السياسية, 2017)
Considers money legal more components of the money supply liquidity, TEMPhas formed a (legal money) figured prominently in the formation of the money supply in Algeria, TEMPhas seen continuous growth, wif an average growth estimated during the period(1990-2000) estimated at 15.9%, while accounted for l7,35% for the period (2000-2014), which means that the legal money form a significant proportion of the size of the money supply (M2) in the economy, dis increase in legal money relative to the money supply is making money from the legal basis of the most Shall were not per-transactions between individuals in the national economy, and the most important factors or determinants leading to it is what we would like to address it through dis paper under the title «determinants of the increasing use of liquidity in the national economy».
تعتبر النقود القانونية اكثر مكونات الكتلة النقدية سيولة، وقد شكلت (النقود القانونية) حيزاً كبيراً في تشكيلها لعرض النقود في الجزائر، فقد شهدت نمواً مستمراً، إذ يقدر متوسط نموها خلال الفترة (1990 م – 2000 م) بحوالي 15.9%، بينما شكلت نسبة 17.35% للفترة (2000 – 2014 م)، ما يعني أن النقود القانونية تشكل نسبة هامة من حجم عرض النقود (M2) في الاقتصاد، هذا الارتفاع في نسبة النقود القانونية إلى عرض النقود هو ما جعل من النقود القانونية أساس معظم – إن لم تكن كل – التعاملات بين الأفراد في الاقتصاد الوطن، واهم العوامل أو المحددات المؤدية إلى ذلك هو ما نود التطرق إليه من خلال هذه الورقة البحثية تحت عنوان "محددات الاستعمال المتزايد للسيولة النقدية في الاقتصاد الوطني".
Keywords: السياسة الإقتصادية -- التنمية الإقتصادية -- النمو الإقتصادي -- التنمية المستدامة -- الأوراق المالية -- السيولة النقدية -- الجزائر -- المجتمع الجزائري -- مستخلصات الأبحاث